8. posvet o ohranjanju in trajnostni rabi rastlinskih genskih virov: Trajni nasadi, zbornik povzetkov - Šiško, Metka (2025)
8th Conference on the Conservation and Sustainable Use of Plant Genetic Resources (PGR): Perennial plantations, Book of Abstracts. The proceedings contain summaries of the presentations of the 8th Conference on the Conservation and Sustainable Use of Plant Genetic Resources (PGR), organized by the University of Maribor, Faculty of Agriculture and Life Sciences, in cooperation with the Ministry of Agriculture, Forestry and Food. The aim of the annual conference is to raise public awareness of the importance of the conservation of plant genetic resources in Slovenia, present new developments in this field, evaluate successes and facilitate the exchange of experiences among participants. Due to limited financial resources, the current activities of the JSRGB focus primarily on the conservation of existing collections of local plant genetic resources for agricultural crops and less on the systematic evaluation of PGRs for their agronomic value, both in ex situ gene banks and in situ in their natural habitats. The central theme of this year’s conference was perennial plantations; in the first session presentations were given on fruit crops, while in the second session presentations were given on perennial vineyards. Finally, possibilities for the conservation of PGR on farms were discussed and the importance of a quality management system for the operation of gene banks was emphasised.
Keywords: quality management; gene bank; perennial crops; traditional plum genotypes; grapevine gene bank